UPAYA PEMERINTAH INDONESIA DALAM MENANGGULANGI KAMPANYE HITAM UNI EROPA TENTANG CRUDE PALM OIL (CPO) TAHUN 2014 - 2018 - Ardiansyah, Emha; Damayanti, Christy; Dipokusumo, GPH (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
Indonesia as an agricultural country is certainly very closely related to its superior products in the form of palm oil which is a determinant of the plantation sector. Palm oil is one of Indonesia's main assets and commodities. The highs and lows of the Indonesian economy are also affected by a small amount of palm oil which is exported or consumed by the domestic community. The European Union is an area where Indonesian palm oil is exported. The level of consumption of palm oil in Indonesia reaches 20%. In the development of the production and consumption of Indonesian palm oil is not always smooth, there are many challenges faced. One of these challenges is the black camping effort or black campaign efforts undertaken, by the European Union. Issues launched are that Indonesian oil palm plants are not environmentally friendly, social conflicts and climate change occur. To deal with these challenges, researchers took data in oil-statistics and the United States Department of Agriculture in 1999-2016. Using the literature study method or through literature review, the results show that social conflict, environmental unrest and climate change, are not derived from oil palm plants which is being planned and developed by Indonesia, but factors. Therefore, through this research, the writer gives a suggestion that Indonesia can open trade through South Asia and in the region, of course with promising quality of palm oil and also with various policies implemented so that trade politics is no longer used as a tool to reap profits by the state -other countries. Keywords: Palm oil, environmentally friendly, social conflict, climate change, sustainable development